Observational test of empirical magnetopause location models using geosynchronous satellite data. Issue 11 (21st November 2016) - Park, Eunsu; Moon, Y.‐J.; Lee, Kangjin
Abstract: In this study, we identify 123 geosynchronous magnetopause crossings using geosynchronous satellite observation data from 1996 to 2010 as well as make an observational test of magnetopause location models using the identified events. For this, we consider three models: Petrinec and Russell (1996), Shue et al. (1998), and Lin et al. (2010). To evaluate the models, we estimate a probability of detection (PoD) and a critical success index (CSI) as a function of year. To examine the effect of solar cycle phase, we consider three different time periods: (1) ascending phase (1996–1999), (2) maximum phase (2000–2002), and (3) descending phase (2003–2008). Major results from this study are as follows. First, the PoD values of all models range from 0.4 to 0.8 for the most of years. Second, the PoD values of Lin et al. (2010) are noticeably higher than those of the other models. Third, the CSI values of all models range from 0.1 to 0.3, and those of Shue et al. (1998) are slightly higher than those of the other models. Fourth, the predicted magnetopause radii based on Lin et al.(2010) well match the observed ones within 1 Earth radius, while those on Shue et al. (1998) overestimate the observed ones by about 2 Earth radii. Fifth, the PoD and critical success index (CSI) values of all the models are better for the solar maximum phase than those for the other phases, implying that the models are more optimized for the phase. Key Points: The PoD and CSI values range from 0.4 to 0.8 and from 0.1 to 0.3, respectively Lin et al. (2010) has the highest PoD values in solar cycle 23 Forecasting of geosynchronous magnetopause crossing depends on solar cycle phase